Modification Reactor Biogas With Isolation Water And Scrubber To Increase Biomethane Production - Afifah, Meita; Prihatini, Chindy Aulia; Syamsuri, Iyappateya Gelegar Dirgantara; Didik, Nurjan; Elsyana, Vida; Ramandani, Adityas Agung (Jurnal Energi Baru dan Terbarukan, 2024)
Biogas is alternative energy produced through the process of fermenting organic materials in anaerobic conditions to produce methane gas (CH4). The quality of the biogas depends on the concentration of the CH4, the higher the content, the better the quality. One way to improve the quality of biogas so that the content of methane gases in biogases increases and can reduce gases such as CO2, H2S, and other gases is by using a scrubber that contains compound fertilizer as its purification. The objective of this research is to reuse organic waste into useful biogas as alternative energy, and to apply water as a methane gas isolator so as not to be wasted on batch and scrubber reactor processes for the purification of H2S content. The old test results of the biogas flame and the color test of the flame on the 20th and 28th days could not be done, because of the little gas formed to the pressure of the gas generated 0 atm. On the 40th day where the gas pressure generated 5 atm, but the results of the biogas fire test did not come out because the gas produced was still small so the flow of gas to the stove did not reach. Biogas production needs to be increased so that the long-standing test of flame and flame color of biogas can be done well. This research also was explored step by step to producing biogas using organic waste. In addition, consideration should be given to the use of other methods to increase gas production so that these alternative energy applications can run optimally.